Cost Efficiency Analysis of Purchasing Imported Elevators Through Customs Clearance Services at PT Marico Gria Jakarta - Lestari, Niken; Hadi, Wartoyo; Wahidhani, Eha Hasni (Institut Bisnis dan Informatika Kesatuan, 2023)
The research was conducted at PT Marico Gria, a company in Jakarta that sells elevators. This research aims to determine the cost efficiency of import purchases through customs clearance and self-management services. Data was collected through interviews, documentation, and literature studies to then be analyzed using a qualitative descriptive method by calculating the amount of relevant costs that have occurred or will come. Efficiency is calculated based on assumptions seen from the company's purchasing potential. The results showed that the calculation of the cost of purchasing imports in one purchase through customs clearance services was greater, namely, IDR 8,550,000, while self-management was IDR 5,000,000. So the company's import purchases in 10 times the purchase per year In the next 5 years the company gets an efficiency of IDR 147,500,000, - if the company carries out customs clearance with self-management. Keyword: Cost efficiency, Import Purchases, Customs Clearance, Self-Management